A comparison between swallowing sounds and vibrations in patients with dysphagia. (June 2017) - Movahedi, Faezeh; Kurosu, Atsuko; Coyle, James L.; Perera, Subashan; Sejdić, Ervin
Highlights: Cervical auscultation refers to sounds or vibrations captured during swallowing. Microphones and accelerometers are common sensors used for cervical auscultation. Open questions exist about information provided by the two sensors about the swallowing function. We investigated these questions in the current manuscript. Details provided by microphones and accelerometers about the swallowing function are unique and these two transducers are not interchangeable. The selection of transducer would be a vital step in future studies. Abstract: The cervical auscultation refers to the observation and analysis of sounds or vibrations captured during swallowing using either a stethoscope or acoustic/vibratory detectors. Microphones and accelerometers have recently become two common sensors used in modern cervical auscultation methods. There are open questions about whether swallowing signals recorded by these two sensors provide unique or complementary information about swallowing function; or whether they present interchangeable information. This study aims to compare of swallowing signals recorded by a microphone and a tri-axial accelerometer from 72 patients (mean age 63.94 ± 12.58 years, 42 male, 30 female), who had videofluoroscopic examination. The participants swallowed one or more boluses of thickened liquids of different consistencies, including thin liquids, nectar-thick liquids, and pudding. A comfortable self-selected volume from a cup or a controlled volume by the examiner from a 5 ml spoon was given to the participants. A broad feature set was extracted in time, information-theoretic, and frequency domains from each of 881 swallows presented in this study. The swallowing sounds exhibited significantly higher frequency content and kurtosis values than the swallowing vibrations. In addition, the Lempel–Ziv complexity was lower for swallowing sounds than those for swallowing vibrations. To conclude, information provided by microphones and accelerometers about swallowing function are unique and these two transducers are not interchangeable. Consequently, the selection of transducer would be a vital step in future studies.